The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jadohealth.2013.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Recruitment of Youth With Type 2 Diabetes Into Clinical Trials

Abstract: Purpose To better understand and overcome difficulties with recruitment of adolescents with type 2 diabetes into clinical trials at three United States institutions, we reviewed recruitment and retention strategies in clinical trials of youth with various chronic conditions. We explored whether similar strategies might be applicable to pediatric patients with type 2 diabetes. Methods We compiled data on recruitment and retention of adolescents with type 2 diabetes at three centers (National Institutes of Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 43 publications
2
78
0
Order By: Relevance
“…There is some evidence for great difficulty in recruiting youth for any type of diabetes-related intervention, especially among minorities. 40,41 …”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for great difficulty in recruiting youth for any type of diabetes-related intervention, especially among minorities. 40,41 …”
Section: Discussionmentioning
confidence: 99%
“…Two additional studies with younger participants also found preferences for e-technologies. In a study of youth with Type 2 diabetes, Nguyen and colleagues (2014) found that monetary incentives and technological approaches (mobile phones and websites) were the most effective strategies to engage and retain participants. In contrast, patients with rheumatoid arthritis, with a mean age of 61 years, preferred to complete research surveys via regular mail, followed by telephone, with the Internet identified as their least preferred method (Garcia et al, 2014).…”
Section: 0 Integrating E-technologies Into Clinical Trial Design Imentioning
confidence: 99%
“…There is a dearth of information in the literature regarding adherence to medication in pediatric patients with type 2 diabetes. One report (10) from a study of youth with type 2 diabetes at three clinical sites concluded that “compliance with medications and doctor’s appointments is suboptimal in youth with type 2 diabetes.” The objective of the current analysis was to identify factors that predicted medication adherence and to examine relationships among adherence, glycemic control, and indices of insulin action in the TODAY cohort.…”
Section: Introductionmentioning
confidence: 99%